Risk Factors Associated With Cerebro-Vascular Accident Ischemic Stroke In Young And Elderly Population.: Pharmaceutical Science-Pharmacology for Drug Discovery - Dr.Sharadha Srikanth; B.Nadia Shulamite; C. Vamsi Mohan; K.Sandeep Reddy; S. Kaveri (International Journal of Life Science and Pharma Research, 2022)
Cerebral ischemic stroke is caused by a blockage in a artery that supplies blood to the brain. The blockage reduces the blood flow and oxygen to the brain leading to the damage or death of brain cells. Aim of our study is to identify and analyze the risk factors of cerebral ischemic stroke in young and elderly patients. The known Non modifiable risk factors are Age, Gender, Race, Family history of stroke, Low birth weight. Modifiable and well documented risk facrors are Hypertension, Sickle cell disease, Atrial fibrillation symptomatic carotid stenosis, Diabetes, Post menopausal hormone therapy, Dyslipidemia. Life style factors-associated with stroke risk Cigarette smoking, Obesity, Over Alcohol consumption, Physical inactivity. Potentially modifiable but less documented risk factors are usage of Oral contraceptives, Migraine, Drug and alcohol abuse, Homocysteine condition, Sleep disordered breathing. A Prospective observational study on risk factors of cerebral ischemic stroke in young and elderly patients was performed from September 2018-February 2019 i.e for 6 months duration in In-patient department of General Medicine in Gandhi Hospital.140 CVA cases were collected, documented, analyzed and results are obtained as follows. Young subjects HTN (60.9%), Alcohol consumption (78%), Smoking (48%), History of stroke (36%), Diabetes mellitus (24%), Obesity (14.6%), Cardio-Vascular diseases (4.8%). Elderly subjects HTN (82.8%), Smoking (79%), Alcohol consumption (72.7), History of stroke (33.3%), Diabetes mellitus (27.2), Obesity (8.8%), Cardio-Vascular diseases (8%). Reporting of Stroke cases in young adults in India was uncommon in few years ago. But our studies now indicate that the incidence of young stroke is on the rise. It has been observed that for the past 4-5 years the occurrence of stroke is seen at age less than 45years.And lifestyle modifications can reduce the rate of risk.